Pelatihan Pembuatan Biochar dari Sampah Organik di Desa Wringinsongo Kecamatan Tumpang Kabupaten Malang - Windi Zamrudy; Mochammad Agung Indra Iswara; Abdul Chalim (Jurnal Pengabdian kepada Masyarakat, 2024)
Wringinsongo Village is one of the partner villages of the Malang State Polytechnic. Located in Malang District and the distance is 18 KM from Malang State Polytechnic. Recently, the problem faced by residents is the amount of garbage caused by the large number of people who inhabit the village, the emergence of tourism sites, and the increasing lifestyle. The emergence of garbage in the yard causes new problems for the social environment, so it needs serious attention. Meanwhile, in the area there are already Temporary Disposal Sites (TPS) and Final Disposal Sites (TPA), but if people just throw garbage continuously the garbage will build up. However, if the community is provided with procedures for processing and managing waste first, then the amount of waste can be reduced. One of the impacts of the development of natural bathing tourism in Wringinsongo village is the emergence of waste problems left by visitors to these tourist attractions. For this reason, it is necessary to find an alternative solution that is easy to do safe for the environment, and does not cause a new impact, which is to be processed into fuel by drying and processing it into biochar. With this technical guidance, it is hoped that it can become an insight into new knowledge of technology development that can be developed on a large scale to overcome the waste problem.